Environmental Education From the Qur'anic Perspective: Ecological Analysis of Surah Ar-Rūm 41 on the Flood and Landslide Crisis in Sumatra - Halimatun Sakdiah; M. Dimas Suhaimi Zein; Muhammad Ghozali Ma'arif; Aisah Nurkhofifah Lubis; Mohammad Al Farabi (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2026)
This study aims to analyze the relevance, ecological messages, and environmental education concepts to prevent floods and landslides in Sumatra in QS Ar-Rūm verse 41. Using a qualitative approach based on literature study, this study examines classical and contemporary interpretations, disaster reports, and scientific literature related to environmental damage. The results of the study indicate that the concept of facade described in the verse is in line with the current ecological crisis triggered by deforestation, land conversion, watershed damage, and irresponsible human behavior. These factors exacerbate disaster risks and make them anthropogenic disasters. The study concludes that Qur'anic ecotheology through the principles of monotheism, caliphate, mizan, and Amanah is an important foundation for environmental education and the formation of ethical-spiritual awareness to prevent ecological damage.